STRATEGI PEMBELAJARAN, LOKASI SEKOLAH, DAN KEMAMPUAN GERAK DASAR SISWA SEKOLAH DASAR - Syahrial Bakhtiar (Universitas Negeri Malang, 2015)
Abstract: Learning Strategies, School Locations, and Fundamental Motor Skills of Elementary School Students. This study is aimed at measuring the effects of learning strategies and school locations on students' fundamental motor skills. It is an experimental study which employs the 2x2 factorial design. The subjects of the experiment were students from elementary schools in Padang who were selected through multi stage random sampling. Data were collected using the TMGD-2 test and analyzed using the two-way ANOVA. The findings of the study show that the fundamental motor skills of the students who are taught with the Game Series Learning Strategy (GSLL) are better than those taught with the Conventional Learning Strategy (CLS). With regard to school locations, the fundamental motor skills of students in the urban areas are better than those in the suburbs. The findings also reveal an interaction of the effects of learning strategies and school locations on the students' fundamental motor skills. The students in the urban areas who learn through the GSLL have better fundamental motor skills than those who learn through the CLS. On the other hand, the students in the rural areas who learn through the GSLL demonstrate lower fundamental motor skills than those who learn through the CLS.    Keywords: learning strategy, physical education, fundamental motor skills Abstrak: Strategi Pembelajaran, Lokasi Sekolah, dan Kemampuan Gerak Dasar Siswa Sekolah Dasar. Penelitian ini bertujuan untuk mengukur perbedaan strategi pembelajaran dan lokasi sekolah siswa berikut interaksinya terhadap kemampuan gerak dasar. Subjek eksperimen adalah seluruh siswa SD kota Padang yang dipilih dengan multi stage random sampling dan menggunakan rancangan faktorial 2x2. Data dikumpulkan dengan tes TGMD-2 dan dianalisis dengan ANAVA dua jalur. Penelitian ini menemukan bahwa kemampuan gerak dasar siswa yang diberi perlakuan Strategi Pembelajaran Rangkaian Permainan (SPRP) lebih baik daripada siswa yang diajar dengan Strategi Pembelajaran Konvensional (SPK). Kemampuan gerak dasar siswa sekolah di kota lebih baik daripada di pinggiran kota. Terdapat interaksi pengaruh strategi pembelajaran dan lokasi sekolah terhadap kemampuan gerak dasar siswa. Kemampuan gerak dasar siswa di kota dan diberi SPRP lebih tinggi daripada siswa dengan SPK. Kemampuan gerak dasar siswa pinggiran kota dan diberi SPRP lebih rendah daripada siswa dengan SPK. Kata kunci: strategi pembelajaran, pendidikan jasmani, kemampuan gerak dasar.